Analisis Stability Berdasarkan IMO Pada Kapal Crew Boat 40M - Bayu Al Fahmi Liddin; Erifive Pranatal (Pusat riset dan Inovasi Nasional, 2023)
Crew Boat is a ship used to transport crews and supply food, water, and equipment to support offshore oil drilling activities. The crew boat 40 M was built at PT. FGH has a hull of 12 people and a passenger carrying capacity of 70 people. This ship also has 3 prime movers so that the ship can go at speeds of up to 25 knots. When the ship operates from the port to the oil drilling site carrying full passengers and other equipment that supports the oil drilling, it is expected that this Crew Boat ship is expected to be able to carry passengers and other equipment stably or not sway. So this research was conducted to determine the stability of the Crew Boat. Ship stability is obtained by modeling using the Maxsurf modeler to make a ship hull model and also using Maxsurf Stability with 3 different loadings. Obtained from the research results of the Crew Boat 40 M ship built at PT.FGH meets the modification criteria with IMO Intact Stability and the ship is suitable for use according to its function.